Correlation between Serum Interleukin-17 level and Serum Reactive Oxygen Species levels among Children experiencing Otitis Media with Effusion - Marwa Abdelhafeez; Noura Mostafa Mohamed (International Archives of Otorhinolaryngology, 2021)
Introduction The detection of inflammatory mediators in the serum of children with have otitis media with effusion (OME) and their correspondence with clinical considerations may enable the use of a modern nonsurgical curative treatment for OME. Objective To determine the relation between interleukin-17 (IL-17) serum level and reactive oxygen species (ROS) serum levels in children suffering from OME and to disclose if any variation occurs in the level of IL-17 Will affect the ROS and antioxidant equilibrium in the serum, which indicates the entire body's reaction to OME. Methods The present study was a case-control study. A total of 24 children experienced OME, and 24 healthy controls were recruited. All participants in the study were subjected to a systematic clinical investigation including otoscopic, audiometric, and tympanometric examination. Also, venous blood samples were collected from all children to determine the levels of IL-17 and ROS. Results The mean ± standard deviation (SD) age ranges of the patients and the control group were 6.8 ± 2.7 and 6.2 ± 3.4 years, respectively. A stylistically significant difference in the levels of serum nitric oxide (NO), catalase (CT), myeloperoxidase (MPO), and malondialdehyde (MDA) (p < 0.05) was detected between OME and control patients. No significant difference was found in serum levels of superoxide dismutase (SOD) and glutathione peroxidase (GPX) between OME and control patients. The serum levels of MDA, NO, and MPO positively correlated with the serum levels of IL-17 in OME patients. Conclusion In the present study, there is a reasonable role of the IL-17 pathway in OME pathogenesis through an increase in ROS levels.